Pengetahuan dan Perilaku Ibu dalam Pencegahan Stunting pada Balita - Ade Devriany; Irma Azzah Rika Niara; Ori Pertami Enardi (Citra Delima Scientific journal of Citra Internasional Institute, 2025)
Stunting is a problem of malnutrition that is still experienced by toddlers in Indonesia. According to the 2022 Indonesian Nutritional Status Study (SSGI), the prevalence of stunting in Bangka Belitung Province is highest in South Bangka Regency, which is 23%. One of the causes is the lack of knowledge and behavior of mothers in preventing stunting. The purpose of this study is to describe the knowledge and behavior of mothers in preventing stunting in toddlers in Serdang Village, South Bangka Regency. This research method uses a quantitative method with a descriptive research design which was carried out in April 2024 in the Serdang Village Area. This study involved 35 mothers who have toddlers aged 3-5 years who were selected using simple random sampling. The results of the study showed that the average age of toddlers aged 4 years was 66.9% with the most gender being female. Mothers of toddlers aged 21-64 years were 97.1% with a good knowledge category of 97.1%. All mothers have good knowledge regarding the characteristics of stunting in children with a percentage of 100%, but 40% of mothers do not know the category of healthy children assessed from their height with their age. As many as 88.6% of mothers have good behavior in preventing stunting by getting used to washing their hands before feeding their children. However, 31.4% of mothers never seek information about stunting. The conclusion of the study is that mothers' knowledge and behavior in preventing stunting are in the good category.